Fostering Hybrid Identity in Hello Talk to Conquer Intercultural Miscommunication - Jessica Iona (Center for Southeast Asian Social Studies (CESASS), 2026)
Global digitalization has increasingly exposed people to diverse cultures worldwide, which, while enriching, also creates greater potential for intercultural miscommunication. Despite this, many individuals still lack adequate Intercultural Communication Competence (ICC) to effectively navigate such challenges. Therefore, fostering hybrid identities through the negotiation of meaning—also known as the grounding process—is essential for enabling more meaningful intercultural dialogue. This study aims to identify adaptive strategies in performing the grounding process by examining a case study of Chinese users navigating intercultural miscommunication while interacting with international peers in Hello Talk Voice Rooms. A qualitative approach is employed through non-participant online observation, further interpreted using Xin’s analytical model, Communication Accommodation Theory (CAT), and foundational concepts of ICC. The findings reveal that language differences and habitual communication styles are the most significant sources of intercultural miscommunication. However, attitudes, beliefs, and levels of open-mindedness also play crucial roles, as both similarities and differences inevitably shape intercultural interactions. Maintaining constructive and respectful dialogue requires avoiding judgment, developing a strong self-concept and cultural awareness, and demonstrating a willingness to adapt one’s behaviour to different contexts. Enhancing language proficiency also contributes significantly to smoother communication. These adaptive strategies have broad global relevance, particularly within Southeast Asia, including Indonesia. Pragmatic negotiation emerges as a powerful tool for strengthening intercultural relationships, fostering mutual collaboration, and enhancing understanding across countries—especially in trade and cultural exchange. Young people, students, and educational institutions in Indonesia can cultivate hybrid identities by utilizing platforms such as Hello Talk and adopting grounding strategies demonstrated by Chinese users to minimize intercultural miscommunication.